Report of intersex individuals from a southeastern Chinese Choroterpes facialis (Gillies, 1951) population (Ephemeroptera: Leptophlebiidae) - Yang, Qing-Yi; Li, Jing; Zhou, Chang-Fa (Zootaxa, 2023)
Previously there were only three cases of mayfly gynandromorphism reported from Asia, occurring in the families Baetidae and Heptageniidae. Here, we report two intersex individuals of Choroterpes facialis (Gillies, 1951) (Ephemeroptera: Leptophlebiidae) from southeastern China. They have similar external morphologies (each having two different eyes, two shortened penes, and female sternum IX) but with one being predominately male and the other being predominately female (one with eggs in the abdomen, but the other apparently with sperm). We believe this to be the first report of a feminized male individual. This phenomenon implies their intersexuality is caused by some similar reasons, such as temperature or parasitism. Remarkably, two intersex specimens found among 1,736 normal individuals shows that gynandromorphism does occur rarely, and only six normal males in the sampling suggest the species C. facialis is partially parthenogenetic at least.